Conformal Antenna for Aerodynamic Drag Reduction in Airborne System - U, Namrutha; Raaza, Arun; S, Ramesh (International Journal of Engineering and Technology, 2018)
The conformal antenna receives more consideration towards the coverage augmentation of contemporary wireless communication systems. The foremost unprejudiced of conformal antenna is to reduce aerodynamic drag in aircraft. Consequently designing frequency reconfigurable conformal antenna has become a key concern in the airborne system. This article reviews the state-of-the-art conformal antenna design by considering the challenges of reducing the aerodynamic drag in the airborne applications. Microstrip patch antennas represent compact antenna that offer a conformal nature and capability of equipped integration with communication system. In this work, microstrip patch antenna is designed for airborne system for drag reduction. The hybrid particle swarm and cuckoo search optimization algorithm is utilized for the length and width. Then the algorithm values are used for the calculation of effective length. The performance of the proposed method is compared with hybrid artificial neural network and firefly, genetic algorithm and analyzed.Â Â